2018
DOI: 10.3390/galaxies6010013
|View full text |Cite
|
Sign up to set email alerts
|

Polarization: A Method to Reveal the True Nature of the Dusty S-Cluster Object (DSO/G2)

Abstract: Abstract:There have been different scenarios describing the nature of a dusty source, noted as Dusty S-cluster Object (DSO) or G2, orbiting around the Galactic centre super-massive black hole. Observing the polarized continuum emission of this source provides information on its nature and geometry. We show that this source is intrinsically polarized with polarization degree of 30%, implying that it has a non-spherical geometry, and a varying polarization angle in the ambient medium of the black hole. Its main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In conclusion, the rotating spots are a viable scenario capable to explain the occurrence about once per day of modulated flares from within a few milli-arcseconds of the Sagittarius A* supermassive black hole. 12,18 However, the astrophysically realistic scenarios have to account not only for the time-scales of gradual dispersion of the orbiting features by tidal effects 1,19 but also for the effects of plasma influencing the light propagation through a non-vacuum spacetime near the black hole. 2,13…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the rotating spots are a viable scenario capable to explain the occurrence about once per day of modulated flares from within a few milli-arcseconds of the Sagittarius A* supermassive black hole. 12,18 However, the astrophysically realistic scenarios have to account not only for the time-scales of gradual dispersion of the orbiting features by tidal effects 1,19 but also for the effects of plasma influencing the light propagation through a non-vacuum spacetime near the black hole. 2,13…”
Section: Discussionmentioning
confidence: 99%
“…LT precession is a genuine gravito-magnetic (Machian) effect of General Relativity (Barbour & Pfister 1995;Ciufolini & Wheeler 1995;Ruffini & Sigismondi 2003); indeed, rotation (spin) of the central object stands behind LT precession and it combines with other influences, for example due to an extended distribution of nearby gravitating matter and/or higher multipoles caused by aspherical deformation (flattening) of the central source of the gravitational field, and the oblateness of the dense nuclear star-cluster (Schödel et al 2014;Neumayer et al 2020). Let us note that attempts to constrain the spin of Sgr A* were already carried out in numerous independent works (Melia et al 2001;Iorio 2011;Fragione & Loeb 2020), however, a definitive answer about the spin orientation is still missing (Shahzamanian & Eckart 2015). While the GRAVITY instrument helped set an upper limit on the extended mass (Heißel et al 2022;Peißker et al 2022), the EHT collaboration revealed the inclination and dimensions of the Schwarzschild radius of Sgr A* (Event Horizon Telescope Collaboration 2022a).…”
Section: Lense-thirring Effectmentioning
confidence: 99%
“…Zajacek, Karas & Eckart 2014, Zajacek et al 2016). Shahzamanian et al (2016) model the DSO as a combination of a bow shock and a bipolar wind of the central star. This model is consistent with the DSO's total flux density and the polarization degree.…”
Section: Infrared Polarimetry Of Sgra*mentioning
confidence: 99%
“…Here we present a brief description of the accretion process acting onto SgrA* from a statistical analysis of emission at different wavelengths. We also explore the geometrical properties of SgrA* accretion flow and of the DSO via infrared polarimetry (Shahzamanian et al 2015(Shahzamanian et al , 2016.…”
Section: Introductionmentioning
confidence: 99%